Healthcare use, costs and quality of life in patients with end-stage kidney disease receiving conservative management: results from a multi-centre observational study (PACKS). (September 2018) - Phair, Glenn; Agus, Ashley; Normand, Charles; Brazil, Kevin; Burns, Aine; Roderick, Paul; Maxwell, Alexander P; Thompson, Colin; Yaqoob, Magdi; Noble, Helen
Background: Previous research has explored the cost of providing renal replacement therapies in patients with end-stage kidney disease and their quality of life. This is the first study to examine the healthcare costs of patients receiving conservative care without dialysis for end-stage kidney disease. This alternative to dialysis is an option for patients who prefer a supportive and palliative care approach. Aim: Descriptive cost and quality of life analyses alongside a UK-based multi-centre observational study in patients receiving conservative management for end-stage kidney disease. Design: Health service use was recorded up to 12 months after making the decision to receive conservative management. Mean costs were calculated for each 3-month time period. The annual cost was calculated in two ways: by using only patients with complete cost data and by using all available data weighted by the number of patients at each time point. Setting: In total, 42 patients who opted for conservative management over dialysis were recruited. Results: Mean costs were £1622 (0–3 months), £1008 (3–6 months), £554 (6–9 months) and £2626 (9–12 months). Mean annual cost based on complete data ( n = 8) was £5511, and the weighted mean annual cost was £5620. Conclusion: The importance of this study is twofold. First, it provides substantive new information for health and social care planning of conservative management by demonstrating where demand exists for services, in both the United Kingdom and other countries with a comparable health service structure. Second, methodologically, it indicates that it is feasible to collect service use data directly from this patient population.